Child Protection / An Introduction - Beckett Chris (Sage Publications, 2005)
This book offers an Introduction to Child Protection Work. Doing Child Protection Work, Different Perspectives, The Child Protection Task, Doing the Job, The Nature and Consequences of Child Maltreatment, Recognizing Child Abuse and Neglect, Disabled Children, Harm, The Causes and Contexts of Child Maltreatment, Causes and Contexts, Parents and Drugs and Alcohol, Parents with Learning Difficulties, Problems and Dilemmas for Child Protection Work, Poverty, Abusive Systems, The Limits of Possibility, References, Index.